Rational Fitting Techniques for the Modeling of Electric Power Components and Systems Using MATLAB Environment - Salvador Banuelos- Cabral, Eduardo; Alberto Gutierrez-Robles, Jose; Gustavsen, Bjorn (IntechOpen, 2017)
The rational fitting processes have become an essential component of electric power components and systems modelling. These techniques allow the inclusion of frequency-dependent effects in electric power systems modelling. There are several methods for carrying out this model synthesis. This book provides a detailed description of some of the most widely used rational fitting techniques for approximation of frequency domain responses. The techniques are Bode's asymptotic approximation, the Levy method, iteratively reweighted least squares, the Sanathanan-Koerner method, the Noda method, vector fitting, the Levenberg-Marquardt method and the damped Gauss-Newton method. Such models permit the inclusion of frequency dependence in the modelling of overhead transmission lines and underground cables, in power transformers at high frequencies and in frequency-dependent network equivalents (FDNE). A MATLAB routine for each technique is presented.